(untitled) (Quaestiones Disputatae: temas en debate, 2018)
In recent times, the studies on St. Thomas Aquinas in Italy have seen, among his most appreciated translators and interpreters, Professor Fernando Fiorentino, former professor of Theoretical Philosophy at the University of Salento. By will of prof. Giovanni Reale, the greatest expert in the whole world of ancient philosophy, especially Platonic and Aristotelian, Professor Fiorentino has been for more than a decade, the expert and privileged translator and commentator of the texts of Saint Thomas for the famous compilation «Il pensiero occidentale», by the well-known Bompiani editorial (Milano).